(untitled) (Research, Society and Development, 2020)
The present work aims to face the theme of the use of bathrooms according to the gender identified in the work environment, starting from the analysis of two legal speeches: one, the understanding that the prohibition of the use of the feminine bathroom by a transsexual employee characterizes off-balance damage, due to affront to the value of human dignity and the right to equality; two, the understanding that moral damage cannot be characterized, given that the said prohibition on the part of the employer is justified due to the preservation of the right to privacy of other users of the bathroom. For this purpose, the proposed investigation will take place through the case study methodology, based on the analysis of the judgment issued in the judgment of Ordinary Appeal No. 000093977.2012.5.09.0003 by the 1st Panel of the Regional Labor Court of the 9th Region. The judgment that is the subject of this article demonstrates that the issue is not peaceful. The first degree decision denied the configuration of moral damage, the second degree judgment recognized it, but, even so, with divergence between the Judges that compose the collegiate judgment body. Finally, the decision that is the object of this investigation is in tune with the need to recognize transsexual workers as human persons like any other and, therefore, cannot suffer discrimination and have their dignity harmed in the work environment.